(untitled) (Annals of Medical Research, 2022)
Aim: To evaluate the changes of vessel densities and retinal nerve fiber layer thicknesses in strabismic amblyopia. Materials and Methods: Fifteen cases with unilateral strabismic amblyopia and 20 healthy subjects were enrolled. The vessel densities in the superficial capillary plexus (SCP), deep capillary plexus (DCP), choriocapillary plexus (CCP), foveal avascular zone (FAZ) and foveal vessel density (FD-300) were assessed using OCT-A (AngioVue, RTVue XR Avanti; Optovue, Inc., Fremont, CA). Retinal nerve fiber layer thickness (RNFLT) measurements were evaluated using SS-OCT. Results: The mean foveal, parafoveal, and perifoveal vessel densities in SCP, DCP, CCP and FAZ area were similar between the amblyopic, fellow and healthy eyes. The RNFLT in all quadrants were higher in amblyopic eyes compared to fellow eyes and controls and the difference was statistically significant in the nasal quadrant (p<0.001). Conclusion: Our results indicate that the vessel densities in retinal vascular plexuses, CCP and FAZ area were similar in amblyopic eyes, fellow eyes and healthy controls. Further large scale studies will be valuable.